Communication Network Analysis At The Mandailing Jaya Coffee Cooperative In Ulu Pungkut District, Mandailing Natal Regency, North Sumatra Province - Suhati, Rizka; Wahyuni, Sri; Basyar, Basril (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Communication problems often occur in organizational groups. This is the case with the Mandailing Jaya Coffee Cooperative, which has experienced communication issues within the organization. These problems have resulted in the accumulation of members’ production and harvest yields in the cooperative’s warehouse. The situation is due to the lack of interaction between cooperative members and the management during member meetings for disseminating information about proper coffee harvesting methods and good coffee harvest criteria. Therefore, this study aims to analyze the communication network of the Mandailing Jaya Coffee Cooperative in Ulu Pungkut District, Mandailing Natal Regency. The method used in this research is a descriptive quantitative method, employing snowball sampling with 118 respondents from four farmer groups affiliated with the cooperative. Data were collected through direct interviews and analyzed using communication network analysis with the Ucinet-Draw application. The results show that the communication network structure of the Mandailing Jaya Coffee Cooperative follows an all-channel structure characterized as a radial personal network. Network centrality identifies the roles of actors in the network, namely the gatekeeper (the cooperative chairman) actor SL, the opinion leader (a cooperative member) actor ISM, and the bridge (a cooperative manager) actor IK within the communication network of the Mandailing Jaya Coffee Cooperative.